Bead‐Based Extracellular Vesicle Analysis Using Flow Cytometry. Issue 12 (25th October 2020) - Yang, Katherine S.; Lin, Hsing‐Ying; Curley, Caleigh; Welch, Marisa W.; Wolpin, Brian M.; Lee, Hakho; Weissleder, Ralph; Im, Hyungsoon; Castro, Cesar M.
Abstract: Extracellular vesicles (EVs) represent promising circulating biomarkers for cancers, but their high‐throughput analyses in clinical settings prove challenging due to lack of simple, fast, and robust EV assays. Here, a bead‐based EV assay detected by flow cytometry is described, which integrates EV capture using microbeads with EV protein analyses by flow cytometry. The assay is fast (<4 h for 48 samples), robust, and compatible with conventional flow cytometry instruments for high‐throughput EV analysis. With the method, a panel of pancreatic cancer biomarkers in EVs from plasma samples of pancreatic cancer patients is successfully analyzed. The assay is readily translatable to other biomarkers or cancer types and can be run with standard materials on conventional flow cytometers, making it highly flexible and adaptable to diverse research and clinical needs. Abstract : A bead‐based extracellular vesicles (EV) assay detected using flow cytometry enables fast, robust, high‐throughput EV analysis. The method combines EV capture using polystyrene beads with EV protein analyses via flow cytometry. The assay can be run with standard materials on conventional flow cytometers, making it highly flexible and adaptable to diverse research and clinical needs.